Progress and perspective of microneedle system for anti-cancer drug delivery. (January 2021) - Li, Dongdong; Hu, Doudou; Xu, Hongxia; Patra, Hirak K.; Liu, Xiangrui; Zhou, Zhuxian; Tang, Jianbin; Slater, Nigel; Shen, Youqing
Abstract: Transdermal drug delivery exhibited encouraging prospects, especially through superficial drug administration routes. However, only a few limited lipophilic drug molecules could cross the skin barrier, those are with low molecular weight and rational Log P value. Microneedles (MNs) can overcome these limitations to deliver numerous drugs into the dermal layer by piercing the outermost skin layer of the body. In the case of superficial cancer treatments, topical drug administration faces severely low transfer efficiency, and systemic treatments are always associated with side effects and premature drug degradation. MN-based systems have achieved excellent technical capabilities and been tested for pre-clinical chemotherapy, photothermal therapy, photodynamic therapy, and immunotherapy. In this review, we will focus on the features, progress, and opportunities of MNs in the anticancer drug delivery system. Then, we will discuss the strategies and advantages in these works and summarize challenges, perspectives, and translational potential for future applications. Graphical abstract: Image 1